(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The impact of SO2 pollution on agricultural as well as physiological and ecological dynamicsat both the individual and community scale. Lentil is a prominent source of protein in India. Plant speciesthat produces pods such as lentil and dry pea are adversely affected by the presence of Sulphur di-oxideresulting in a reduction in their overall output. In present study chlorophyll content extracted from lentilplant leaves treated with different concentration of SO2 and prepared sample were exposed to a range oflight having different wavelength and analyzed using a Spectrophotometer and calculation of chlorophylla and b using by Arnon method (1949). It is concluded that Chlorophyll content was higher in lowconcentration and reduced gradually with higher concentration.